2014
DOI: 10.1007/s00392-014-0792-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning of adults with congenital heart disease: outcomes of a 30–43 year longitudinal follow-up

Abstract: At 30-43 year follow-up, compared to normative data, patients had a better quality of life and emotional functioning, despite impairments on occupational level and income. Compared to patients with simple defects, patients with moderate/complex ConHD scored worse on multiple outcomes, which warrants special attention for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…41,42 Problems with executive functioning likely contribute at least in part to functional differences in adults with CHD, including lower occupational status and not living independently from parents. 29 Indeed, findings from the current study highlight weaker executive functioning skills for those who received disability benefits. It is also likely that problems with executive skills contribute to barriers in ongoing cardiology care given the complexities of decision making and potential for emotional and cognitive overwhelm.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…41,42 Problems with executive functioning likely contribute at least in part to functional differences in adults with CHD, including lower occupational status and not living independently from parents. 29 Indeed, findings from the current study highlight weaker executive functioning skills for those who received disability benefits. It is also likely that problems with executive skills contribute to barriers in ongoing cardiology care given the complexities of decision making and potential for emotional and cognitive overwhelm.…”
Section: Discussionmentioning
confidence: 59%
“…Adults (ages 30-43 years) with CHD had lower occupational status and yearly income, a higher percentage were living with their parents, and those with moderate to severe CHD experienced higher physical restrictions (e.g., play sports, perform physical labor), reduced physical strength, and endorsed feeling more at a disadvantage in life. 29 Those with severe CHD (i.e., single ventricle) compared with the general population had lower rates of employment, especially females. 30 There is extremely limited information about the neuropsychological functioning (e.g., intelligence, language, nonverbal skills, memory, academic, sensory and motor, executive functioning) of adults with CHD.…”
mentioning
confidence: 99%
“…Among adults with CHD, lower self-reported family income has been associated with greater complaints of somatic symptoms [4] and worse exercise intolerance [29], while a higher income has been identified as a protective factor for loss to follow-up [30]. Conversely, Opić and colleagues (2015) compared adults with CHD to normative data in the Netherlands and found that adults with CHD had lower income as compared to norms, but reported higher QoL [31]. Opić and colleagues did not report the relationship between income and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The employment of adults with CHD (ACHD) has been investigated in many countries. Overall, the rate of patient employment is reported to be 50–80% for full‐time and part‐time workers, and the rate of unemployment ranges from a small percentage to more than 10% . ACHD generally have a lower employment rate than do individuals without CHD, although this varies by country.…”
mentioning
confidence: 99%
“…Overall, the rate of patient employment is reported to be 50-80% for full-time and part-time workers, and the rate of unemployment ranges from a small percentage to more than 10%. [1][2][3][4][5][6] ACHD generally have a lower employment rate than do individuals without CHD, although this varies by country. For example, according to a study in the UK, 7 the unemployment rate was reported to be 33% (excluding students and retired people), which suggests that these patients faced significantly greater difficulty in finding employment than others because the average unemployment rate was 8.3% in the area of investigation.…”
mentioning
confidence: 99%